Fire Behavior of Lightweight Reinforced Concrete Deep Beams and Enhanced Structural Performance via Varied Stirrup Spacing – An Integrated Study - Ali Ali; Amir Akhaveissy; Bahaa Abbas (Journal of Rehabilitation in Civil Engineering)
The behavior of lightweight reinforced concrete deep beams (LRCDBs) under fire conditions is investigated in this study, with a specific focus on the effect of varying transverse reinforcement spacing. Four LRCDB specimens with transverse reinforcement intervals of 60 mm and 150 mm are constructed and subjected to four-point bending tests at both normal and elevated temperatures. The ultimate load-bearing capacity of the specimens is increased by 6.9% when the spacing of transverse reinforcements is reduced from 150 mm to 60 mm. Additionally, the load-bearing capacity of the specimens with 60 mm and 150 mm stirrup spacing is reduced after exposure to fire, with reductions of 16.8% and 23.6% respectively. The ultimate deflection of the mid-span of the beam is also diminished by the heat from the fire. The analysis of the specimens is performed using Abaqus software and the Finite Element Method. The obtained results exhibit a strong agreement with the experimental data, providing valuable insights into the behavior of LRCDBs during fire conditions. These insights highlight the critical importance of designing appropriate transverse reinforcement.